The Concept of Being in the Philosophy of Hegel and Kierkegaard - Šliogeris, Arvydas (Problemos, 1977)
The article deals with the comparative analysis of the interpretation of the concept of being as conceived in classical German philosophy, in G. Hegel’s works in particular, and as developed in post-Hegelian philosophy, in Marxism and S. Kierkegaard’s religious philosophy. As it is shown in the article, Hegel brings to an end the centuries old tradition of West-European philosophy of thinking and being dominated by the unity in which being was dissolved in the structures of cognition and was deprived of independent ontological significance as a reality beyond the logical universe. The concept of being received a radically new interpretation in the works of K. Marx and F. Engels. In Marxist conception, being is regarded as a materj.al reality integrated into the sphere of practically transforming and socially determined human existence. The traditional understanding of the concept of being was rejected by the Danish religious thinker S. Kierkegaard. He also severed the unity of being and thinking, but contrary to Marx, he interpreted being irrationally which he understood as the individual spiritual existence of man immersed in religious passion.